ANALISIS POLA PRODUKSI KARET (STUDI KASUS DI DUSUN TIBU MANDAU KABUPATEN SINTANG) - B01108031, Wili Brodus (Jurnal Pembangunan dan Pemerataan, 2013)
This research entitled Analysis of Rubber Production Pattern (Case Study in Dusun Tibu Mandau, Sintang District). This research is to understand and analyzes the production pattern towards income which gained by rubber tapper in Dusun Tibu Mandau Sintang District While, responden from government official said that the method which have been being aplicated by community in Dusun Tibu Mandau has no appropriate with the cultivation pattern which recomended by government. He also said that the plant spacing, use of superior seeds, pest controlling and treatment are very important thing in rubber cultivation. Working relationships and sharing system pattern is a pattern that is applied by the Dusun community Tibu Mandau with couple of factors considerations in implementing labor relations still had ties of kinship and pattern sharing system were implemented, an option that the owner applied to workers who want to work on rubber plantations garden owners. Land ownership patterns in the hamlet Tibu Mandau, land ownership by clearing fields and fields that are opened wide by the public or hereditary land ownership is done, the legacy of the family. Institutional role in growing cultures entrepreneurship, more institutional agencies interpret the norms of values??, traditions and culture of the institutions that form the institutional and entrepreneurial menumbuhakan, the institutions established by the public so that institutional as capital in entrepreneurship. Key word: Pattern rubber production